1986
DOI: 10.2337/diab.35.5.503
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin and Oral Glutathione on Glutathione Levels and Superoxide Dismutase Activities in Organs of Rats With Streptozocin-Induced Diabetes

Abstract: The effect of insulin or glutathione treatment on glutathione content of liver and jejunal mucosa and on superoxide dismutase (SOD) activity of liver, kidney, and erythrocytes was investigated in pair-fed animals with streptozocin (STZ)-induced diabetes. Diabetes lowered hepatic glutathione concentration, but glutathione concentration of the jejunal mucosa was not affected. Insulin, but not oral glutathione, restored hepatic glutathione concentration to normal levels. Diabetes depressed activity of the cytosol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
65
0
7

Year Published

1991
1991
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 0 publications
12
65
0
7
Order By: Relevance
“…In our study, the level of hepatic, pancreatic and renal GSH was reduced in diabetic mice, which is consistent with an earlier report (43). The decrease in tissue's GSH content could be the result of decreased synthesis or increased degradation of GSH by oxidative stress that prevails during diabetes (44). Furthermore, lipid peroxidation is one of the characteristic features of chronic diabetes (45).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, the level of hepatic, pancreatic and renal GSH was reduced in diabetic mice, which is consistent with an earlier report (43). The decrease in tissue's GSH content could be the result of decreased synthesis or increased degradation of GSH by oxidative stress that prevails during diabetes (44). Furthermore, lipid peroxidation is one of the characteristic features of chronic diabetes (45).…”
Section: Discussionsupporting
confidence: 92%
“…Decreased intestinal GSH level in diabetic rats could be the result of either decreased synthesis or increased destruction of GSH by oxidative damage (Loven et al, 1986). In our study treatment with AGLE and glibenclamide resulted in the increase of GSH and this may be due to either increased biosynthesis of GSH or reduced oxidative stress or both.…”
Section: Discussionsupporting
confidence: 48%
“…Reports have shown that ethanolic extract of Sphaeranthus indicus exhibited protective effect against lipid peroxidation and normalized repressed SOD, CAT, glutathione S-transferase activities in gentamicin induced nephrotoxic rats. 22 In the same vein, previous reports showed that S-IDR treated with exogenous SOD and GSH ratio exhibited improved antioxidant enzymes activities 1,24 which implied amelioration of tissue oxidative stress.…”
Section: -21mentioning
confidence: 86%
“…Another study, 24 posited that decreased Cu-Zn SOD activity observed in DM was sequel to the inactivation of the enzyme as a result of absence or failure to metabolize hydrogen peroxide via GPOx pathway. The decreased levels of renal and hepatic SOD activity of HyGR showed evidence of restoration of the enzyme activity that were comparable to NORM rats following the administration of the various experimental herbal formulations ( Figure 2).…”
Section: -21mentioning
confidence: 99%